Pengaruh Konten Youtube “Bang Tutorial” Terhadap Minat Belajar Mengedit Video Pada Mahasiswa Broadcast - Muhammad Alawi; Rosita Anggraini (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
YouTube is a social media that is widely enjoyed and has a variety of information, one of which, tutorial content that is quite loved by the Indonesian people. One of the YouTube channels that package and display tutorial content is